Plesiomonas shigelloides Septicemia and Meningitis in a Neonate - Julian D Eason; Donlim Peacock (Canadian Journal of Infectious Diseases)
A newborn infant is described who presented with septicemia and meningoencephalitis caused by Plesiomonas shigelloides, a Gram-negative rod belonging to the family Vibrionaceae. This appears to be the first documented case in a neonate in Canada. Despite prompt treatment with appropriate antibiotics, he developed endophthalmitis and lytic brain lesions.